Nilai Interaksi Simbol Tradisi dalam Wujud Pelinggih pada Ruang Publik - I Nyoman Larry Julianto; Made Jodog; Imam Santoso (LP2M ISBI Bandung, 2016)
ABSTRACT In public space in North Bali, there has been concept change of symbol tradition visualiza- tion in the form of pelinggih which is in the form of car. But its essential function as a place of worship has not changed. The surrounding community can accept that phenomenon as adop- tion process and identity of cultural heritage.Through qualitative research, try to be understood a ‘creative process’ outside ‘context of the self’ in communicating the message through visual media. From this research stated that visual form of pelinggih not only the expression result of beauty, but also to communicate the message. Ritual principles of a pelinggih is still maintained. Its materialization concept has undergonenovelty identity due to unification of aesthetic value, art, spiritual and ‘moderniza- tion’ in the context of ‘worldly’ life. Symbol visualization in an effort to communicate that message, contains elements of cultural system acculturation of today’s society to mutually in- teract. Keywords: symbol tradition, visual change, identity of novelty, public space ABSTRAK Pada ruang publik di Bali Utara, terjadi perubahan konsep visualisasi simbol tradisi dalam wujud pelinggih, yakni berbentuk mobil. Fungsi esensinya sebagai tempat pemujaan tidak berubah. Masyarakat sekitar dapat menerima fenomena tersebut sebagai proses adopsi dan identitas warisan budaya.Melalui penelitian kualitatif, berupaya dipahami sebuah ‘proses kreatif’ diluar ‘konteks diri’ dalam mengomunikasikan pesan melalui media visual. Dari penelitian ini, dinyatakan bahwa wujud visual pelinggih tidak hanya hasil ekspresi keindahan, tetapi juga mengomunikasikan pesan. Prinsip–prinsip ritual sebuah pelinggih tetap dipertahankan. Konsep perwujudannya mengalami identitas kebaruan akibat dari penyatuan nilai estetis, seni, spiritual serta ‘modernisasi’ dalam konteks kehidupan ‘duniawi’. Visualisasi simbol dalam upaya mengomunikasikan pesan tersebut, mengandung unsur–unsur akulturasi sistem budaya masyarakat masa kini untuk saling berinteraksi. Kata kunci : simbol tradisi, perubahan visual, identitas kebaruan, ruang publik